2014
DOI: 10.1007/7854_2014_282
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models and Pharmacology of Herpetic and Postherpetic Pain

Abstract: Varicella-zoster virus (VZV) causes varicella upon primary infection and subsequently becomes latent in the sensory ganglia. Reactivation of latent VZV in the sensory ganglion results in herpes zoster, which usually begins with pain and dysesthesia. Pain that persists long after healing of the rash is termed postherpetic neuralgia. VZV inoculation into rats induces mechanical allodynia and thermal hyperalgesia without causing herpes zoster. As with VZV, herpes simplex virus 1 (HSV1) is an alphaherpesvirus. HSV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Patients with PHN often exhibit profound mechanical allodynia and impairment of thermal sensitivity [9,10]. While mechanical allodynia and hyperalgesia can be induced by an inoculation with varicella zoster virus or herpes simplex virus type 1 on the hind paw of rats or mice, the viral infection models are often incapable of inducing thermal impairment and have the shortcoming of developing tissue inflammation, skin lesions, and paralysis through spreading of the virus in the central nervous system [11][12][13]. Previous studies have demonstrated that systemic treatment with resiniferatoxin (RTX), an ultrapotent transient receptor potential vanilloid 1 (TRPV1) agonist, generates long-lasting paradoxical changes in thermal and mechanical sensitivities and can replicate the unique clinical symptoms of patients with PHN [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with PHN often exhibit profound mechanical allodynia and impairment of thermal sensitivity [9,10]. While mechanical allodynia and hyperalgesia can be induced by an inoculation with varicella zoster virus or herpes simplex virus type 1 on the hind paw of rats or mice, the viral infection models are often incapable of inducing thermal impairment and have the shortcoming of developing tissue inflammation, skin lesions, and paralysis through spreading of the virus in the central nervous system [11][12][13]. Previous studies have demonstrated that systemic treatment with resiniferatoxin (RTX), an ultrapotent transient receptor potential vanilloid 1 (TRPV1) agonist, generates long-lasting paradoxical changes in thermal and mechanical sensitivities and can replicate the unique clinical symptoms of patients with PHN [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanical allodynia and mechanical hyperalgesia generally last for 21 days ( 34 , 36 ). In this model, the thermal hyperalgesia are not observed during the outbreak and presence of herpes, but was induced in the post-herpes phase ( 49 ).…”
Section: The Development Of Phn Rodent Models and Pain Evaluationsmentioning
confidence: 99%
“…Different from the other neuropathic pain, VZV establishes a latent infection in the host. No evidence proved that VZV could proliferate in the nervous system ( 49 ), but viral DNA and transcripts have been detected in the DRG of the rodents after infection ( 34 , 51 ). Some reports suspect that transcription of VZV genes within virus-infected neurons may lead to the chronic pain, either through induction of inflammatory mechanisms or through expression of proteins, such as transcriptional regulators that alter host cell expression patterns.…”
Section: Phn Pathogenesis Learned From Rodent Modelsmentioning
confidence: 99%